2007
DOI: 10.1111/j.1365-313x.2007.03149.x
|View full text |Cite
|
Sign up to set email alerts
|

The rice bHLH protein OsIRO2 is an essential regulator of the genes involved in Fe uptake under Fe‐deficient conditions

Abstract: SummaryIron (Fe) deficiency is a major abiotic stress in crop production. Although responses to Fe deficiency in graminaceous plants, such as increased production and secretion of mugineic acid family phytosiderophores (MAs), have been described, the gene regulation mechanisms related to these responses are largely unknown. To elucidate the regulation mechanisms of the genes related to Fe acquisition in graminaceous plants, we characterized the Fe-deficiency-inducible basic helix-loop-helix transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
272
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 293 publications
(287 citation statements)
references
References 39 publications
14
272
1
Order By: Relevance
“…OsVP1, AK109920, and AK101356 were also constitutively expressed in roots and leaves, but AK072874 expression was not detected in these organs (data not shown). These results are in accordance with our previous microarray experiment using rice 22k array slides (10,11,27), which also indicated that IDEF1, in addition to OsVP1, is clearly expressed in germinating seeds (data not shown). Because of the substantial expression of IDEF1 in vegetative organs, in contrast to little expression of AK072874, which constitutes the subgroup of IDE1/Sph/RY-binding factors with IDEF1 ( Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…OsVP1, AK109920, and AK101356 were also constitutively expressed in roots and leaves, but AK072874 expression was not detected in these organs (data not shown). These results are in accordance with our previous microarray experiment using rice 22k array slides (10,11,27), which also indicated that IDEF1, in addition to OsVP1, is clearly expressed in germinating seeds (data not shown). Because of the substantial expression of IDEF1 in vegetative organs, in contrast to little expression of AK072874, which constitutes the subgroup of IDE1/Sph/RY-binding factors with IDEF1 ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…For the detection of endogenous IDEF1 transcripts, rice (cv. Nipponbare) seedlings were grown hydroponically (8,10). Transgenic tobacco and rice plants were grown as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OsIRO2, which is induced by Fe deficiency and is positively regulated by IDEF1, binds to the CACGTGG element to activate another subset of Fe-deficiencyresponsive genes, including two transcription factor genes: OsNAC4 and the AP2 domain-containing gene. These transcription factors may then regulate Fe-deficiency-responsive genes lacking IDEs and CACGTGG in their promoter regions [44]. The induced expression of IDEF1 in transgenic rice plants would effectively strengthen the overall regulatory pathway to confer tolerance to Fe deficiency.…”
Section: Nt Line13 Line12mentioning
confidence: 99%